Comparison of HDO measurements from Envisat/MIPAS with observations by Odin/SMR and SCISAT/ACE-FTS - Lossow, Stefan; Steinwagner, J.; Urban, Joachim; Dupuy, E.; Boone, C. D.; Kellmann, S.; Linden, A.; Kiefer, M.; Grabowski, U.; Glatthor, N.; Höpfner, M.; Röckmann, T.; et al. (Atmospheric Measurement Techniques, 2011)
Measurements of thermal emission in the mid-infrared by Envisat/MIPAS allow the retrieval of HDO information roughly in the altitude range between 10 km and 50 km. From June 2002 to March 2004 MIPAS performed measurements in the full spectral resolution mode. To assess the quality of the HDO data set obtained during that period comparisons with measurements by Odin/SMR and SCISAT/ACE-FTS were performed. Comparisons were made on profile-to-profile basis as well as using seasonal and monthly averages. All in all the comparisons yield favourable results. The largest deviations between MIPAS and ACE-FTS are observed below 15 km, where relative deviations can occasionally exceed 100%. Despite these deviations in the absolute amount of HDO the latitudinal structures observed by both instruments are consistent in this altitude range. Between 15 km and 20 km there is less good agreement, in particular in the Antarctic during winter and spring. Also in the tropics some deviations are found. Above 20 km there is a high consistency in the structures observed by all three instruments. MIPAS and ACE-FTS typically agree within 10%, with MIPAS mostly showing higher abundances than ACE-FTS. Both data sets show considerably more HDO than SMR. This bias can be explained basically by uncertainties in spectroscopic parameters. Above 40 km, where the MIPAS HDO retrieval reaches its limits, still good agreement with the structures observed by SMR is found for most seasons. This puts some confidence in the MIPAS data at these altitudes.